Awareness, perception and acceptability of digital physiotherapy intervention among Malaysian physiotherapist - Rajkumar Krishnan Vasanthi; Lee Cai Ling; Yughdtheswari Muniandy (Intelektual Pustaka Media Utama, 2021)
Digital health intervention (DHI) can solve the patient's problem, such as geographical inaccessibility, delayed provision of care, low-level adherence to clinical protocols, and financial burden. DHI does not necessary to work as a substitution for a functioning health system but helps strengthen its function. Therefore, this study aimed to determine the awareness, perception, and acceptability of digital physiotherapy intervention (DPI) among Malaysian physiotherapists. A total of 209 practicing physiotherapists representing all the regions in Malaysia participated in this online self-reported questionnaire, including demographics profile, continuous professional development, awareness, perception and acceptability of DPI. Analyzed the collected data to determine the knowledge of DPI by using descriptive statistical methods. A 75.1% of the Malaysian physiotherapist aware of digital physiotherapy intervention, 69.38% perceived it reduces the cost for face to face, reduce the time for traveling 47.85%, improve adherence to exercises 42.58%, 78% of them agree with the DPI and 75.1% of them accepted to recommend the digital tools to their patient. Malaysian physiotherapists are aware, agree and recommend the digital physiotherapy intervention to their treatment plan. However, it should still raise awareness about digital physiotherapy intervention to lead them to the future. Developing new digital tools, utilization, and overcoming the various healthcare institutions' low acceptability considering the cost, conventional interventions, and time-consuming should be strategized in Malaysia.